France : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for France. (IMF Staff Country Reports; Country Report, 2010)
The French economy weathered global crisis better than most of its peers. The authorities have taken important policy actions to stabilize the financial system and have implemented suitable fiscal stimulus to cushion the downturn. Executive Directors welcomed the policy, which aims to strengthen the economy through fiscal consolidation, recovery of financial system, improving financial regulation, and also implementing structural reforms to raise potential growth, create jobs, and strengthen competitiveness. They stressed the importance of a multiyear budget framework to enhance the credibility of the consolidation effort.